Ritual Bancakan Sepasaran Bayi sebagai Ruang Liminalitas untuk Membangun Guyub Rukun Masyarakat di Kartasura - Ariyanto, Dani; Lattu, Izak Y. M.; Tampake, Tony R. C.; Suprabowo, Gunawan Y. A. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
The era of globalisation, which is marked by the sophistication of information technology, has affected the fading of local traditions, including the bancakan sepasaran bayi ritual, and the weakening of guyub rukun. Religious fundamentalism and radicalism contribute to undermining guyub rukun in society. Building guyub rukun can be done through the bancakan sepasaran bayi ritual. This article aims to describe and analyse the formation of liminal space in the bancakan sepasaran bayi ritual, which contributes to building guyub rukun in Kartasura. The research method used is post-positivism qualitative method. Interviews were conducted using purposive sampling technique to families who were considered to have the information needed in the research. The result is that through the liminal space contained in the bancakan sepasaran bayi ritual, the community is prepared to build guyub rukun in Kartasura.